412-Positive mesodermal cells and the gonadal mesoderm are separate from the fat-cell lineage. - Tan, C.; Price, C.; Hoshizaki, D.K. (Genetica, 1996)
The Drosophila retrotransposon, 412, is expressed in a cell-specific manner during embryogenesis. At stage 11, 412 transcripts are present in bilateral clusters of cells within the mesoderm. The posterior clusters of 412-positive cells become associated with the gonads at stage 13; however, the fate of the cells in the remaining clusters is unknown. We have tested by in situ hybridization to whole-mount embryos the possible identity of these cells with known precursor cell types present in bilateral clusters. We simultaneously located the 412-positive cells and the precursor cells to visceral muscle or the fat body. We have determined that the 412-positive cells do not correspond to these precursor cells and that the development of the visceral muscle or fat body does not affect the expression of 412 during embryogenesis.